7. Ecological genomics of the Northern krill: Genome-scale comparisons of adaptive divergence - Wallberg, Andreas; Unneberg, Per (Uppsala University, 2024)
This item holds multiple tar archives with genome-scale comparisons of divergence between Northern krill populations, including estimated allele-frequencies and divergence (e.g. FST) , and extended haplotype signatures (XP-nSL estimates). Many analyses were performed in "chunks" (160 in total across both gene-rich and gene-poor sequences), which are described in a previous item.

Population definitions

Population definitions are the same as desribed in a different item:


- "at vs. me" = Atlantic Ocean samples (n=67) vs. the Mediterranean (i.e. Barcelona) samples (n=7).

- "we vs. ea" = South-West North Atlantic Ocean (n=20) vs. North-East North Atlantic Ocean (n=47). In files using this contrast, sometimes the label "wa" is used instead of "we" for the South-West North Atlantic Ocean samples.



Contents:


- allele_freqs_fst.gene_rich_sequences.at_vs_me.tar, contains per-SNP estimates of allele frequencies and FST between "at" and "me" groups along gene-rich sequences.

- allele_freqs_fst.gene_rich_sequences.we_vs_ea.tar, as above but between "we" and "ea" groups.

- allele_freqs_fst.gene_poor_sequences.at_vs_me.tar, contains per-SNP estimates of allele frequencies and FST between "at" and "me" groups along gene-poor sequences.

- allele_freqs_fst.gene_poor_sequences.we_vs_ea.tar, as above but for "we" and "ea" groups.

- allele_freqs_fst.merged_sequences.at_vs_me.csv.gz, contains per-SNP estimates of allele frequencies and FST between "at" and "me" merged into a single TSV file.

- allele_freqs_fst.merged_sequences.we_vs_ea.csv.gz, as above but for "we" and "ea".

- allele_freqs_fst.gene_rich_sequences_windows.at_vs_me.tar.gz, contains per-window estimates of FST between "at" and "me" groups along gene-rich sequences.

- allele_freqs_fst.gene_rich_sequences_windows.we_vs_ea.tar.gz, as above but for "we" and "ea" groups.

- allele_freqs_fst.gene_poor_sequences_windows.at_vs_me.tar.gz, contains per-window estimates of FST between "at" and "me" groups along gene-poor sequences.

- allele_freqs_fst.gene_poor_sequences_windows.we_vs_ea.tar.gz, as above but for "we" and "ea" groups.

- selscan_xpnsl.gene_rich_sequences.tar.gz, contains per-SNP cross-population XP-nSL statistics for gene-rich sequences.

- selscan_xpnsl.gene_poor_sequences.tar.gz, contains per-SNP cross-population XP-nSL statistics for gene-poor sequences.

- selscan_xpnsl.gene_rich_sequences_windows.tar.gz, contains per-window cross-population XP-nSL statistics for gene-rich sequences.

- selscan_xpnsl.gene_poor_sequences_windows.tar.gz, as above but for gene-poor sequences.

- fst_vs_xpnsl.per_snp.at_vs_me.csv.gz, contains per-SNP FST, genomic region and XP-nSL values in a single file for the "at vs. me" contrast.

- fst_vs_xpnsl.per_snp.we_vs_ea.csv.gz, contains per-SNP FST, genomic region and XP-nSL values in a single file for the "we vs. ea" contrast.

- fst_vs_xpnsl_vs_diversity_vs_regions.merged_sequences.at_vs_me.tsv.tar.gz, integrates window-based statistics into a single file for the "at vs. me" contrast.

- fst_vs_xpnsl_vs_diversity_vs_regions.merged_sequences.we_vs_ea.tsv.tar.gz, as above but for the "we vs. ea" contrast.



allele_freqs_fst.gene_(rich|poor)_sequences.(at_vs_me|we_vs_ea).tar

The TSV files in these archives contain per-SNP estimates of allele frequencies and FST, along with SNP annotations. There are nine main fields/columns with overlapping/redundant information to accommodate flexible parsing. Large fields have nested subfields that are separated by "|" (first level) or ":" (second level).


- name of sequence (e.g. "seq_s_1")

- position of SNP (e.g. "448878")

- reference allele (e.g. "A")

- alternate allele (e.g. "G")

- major column with FST value and allele frequency and other data for each population. It is described below.

- type of SNP (e.g. intron, synonymous, missense, intergenic, ...) and label of associated gene (e.g. missense|REF_STRG_1_4_XLOC_012878)

- FST tag and value (e.g. fst|0.0653)

- region, type of SNP and gene label (e.g. region|missense|REF_STRG_1_4_XLOC_012878)

- gene annotation derived from EnTAP annotations and Drosophila homologs, which are described below. Uses comma-separated sub-fields.



Subfields in field 5:

Example:

at/me:0.0653:148:1.0000:1.0000:1.0000|at,134,133.0000,1.0000,0.9925,0.0075|me,14,13.0000,1.0000,0.9286,0.0714

This field splits into three major subfields on "|": one about the pairwise comparison and two with metadata about each population.

1st subfield (at/me:0.0653:148:1.0000:1.0000:1.0000)


- name of contrast (at/me)

- FST of SNP (0.0653)

- Sample size (148)

- Proportion of observed data given overall sample size (1.0000),
Keywords: Biological adaptation; Evolutionary ecology; Genomics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik; Biological Sciences; Biologi; Ecology; Ekologi